2022
DOI: 10.1038/s41598-022-14272-0
|View full text |Cite
|
Sign up to set email alerts
|

AGE/RAGE axis regulates reversible transition to quiescent states of ALK-rearranged NSCLC and pancreatic cancer cells in monolayer cultures

Abstract: Cancer recurrence due to tumor cell quiescence after therapy and long-term remission is associated with cancer-related death. Previous studies have used cell models that are unable to return to a proliferative state; thus, the transition between quiescent and proliferative states is not well understood. Here, we report monolayer cancer cell models wherein the human non-small cell lung carcinoma cell line H2228 and pancreatic cancer cell line AsPC-1 can be reversibly induced to a quiescent state under hypoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…An increase in cellular ROS is the most common promoter of these three processes. Genomic instability is mediated by an increase in ROS levels and damage to nuclear nucleosides and inducing minority MOMP (mitochondrial outer membrane permeabilization) [ 10 ]; quiescence evasion is conducted by an increase in cellular ROS and following the activation of the Ras pathway [ 29 , 30 ]; Section 3 summarizes how mitochondria are involved in EMT. ROS is a double-edged sword, destroying cancer cells at high levels and promoting cancer progression at moderate levels.…”
Section: The Pivotal Role Of Mitochondria In Cancer Cells’ Metabolismmentioning
confidence: 99%
“…An increase in cellular ROS is the most common promoter of these three processes. Genomic instability is mediated by an increase in ROS levels and damage to nuclear nucleosides and inducing minority MOMP (mitochondrial outer membrane permeabilization) [ 10 ]; quiescence evasion is conducted by an increase in cellular ROS and following the activation of the Ras pathway [ 29 , 30 ]; Section 3 summarizes how mitochondria are involved in EMT. ROS is a double-edged sword, destroying cancer cells at high levels and promoting cancer progression at moderate levels.…”
Section: The Pivotal Role Of Mitochondria In Cancer Cells’ Metabolismmentioning
confidence: 99%
“…Reversible, plastic resistance in prostate, breast, colon, pancreatic, and non-small cell lung cancer cell line models has been shown to be a consequence of nutrient deprivation which introduces ROS and low cell proliferation, priming cells to adapt to anti-tumor agents such as the mitochondrial ETC Complex I inhibitor metformin ( Marini et al, 2016 ; White et al, 2020 ; Kadonosono et al, 2022 ). To capitalize on this adaptation, cancers such as colon or breast could be treated with metabolic inhibitors to prevent oxphos or glycolysis mediated adaptations ( Marini et al, 2016 ).…”
Section: Therapy-induced Rewiring Of Mitochondrial Metabolism: Eviden...mentioning
confidence: 99%
“…Therefore, one may conclude that quiescence evasion is orchestrated by another transcription factor. Recent evidence on a non-small cell lung cancer (NSCLC) model demonstrated that this process is regulated by Ras, Rap1, PI3K/Akt, and ERK signaling pathway [ 86 ]. Moreover, it has been noted that mitochondria are indexed actors in Ras-mediated cancer proliferation.…”
Section: Mitochondria’s Benefits For Cancer Cellsmentioning
confidence: 99%